Life cycle cost analysis of CO2 compression processes coupled with a cryogenic distillation unit for purifying high-CO2 natural gas. (June 2022) - Park, Ki-Heum; Lee, Jae W.; Lim, Youngsub; Seo, Yutaek
Abstract: Novel compression processes coupled with a cryogenic distillation unit are designed in this study to purify high-CO2 natural gas or biogas before injection into the reservoir. Four different designs are evaluated to achieve the required injection pressure and minimize both the capital and operation costs. Depending on the pressure–temperature pathway for the compression of the top and bottom products of the distillation unit, the energy and equipment costs are quantified using process simulation models and economic analysis tools, which are integrated with the flow simulation model to determine the required injection pressure. This holistic approach of integrating the compression process and injection pipeline is efficient for optimizing the process design and operation variables. The results suggest that liquefying the top product followed by mixing with the bottom product is the most cost-effective method, as it eliminates costly compressors and simplifies the process configuration. In addition to the life cycle cost analysis of the process, the sudden release of CO2 from the vessel is also studied experimentally. The results show that releasing gaseous CO2 through the valve induces the formation of solid CO2 inside the vessel before complete removal of CO2 from the vessel, thus requiring a controlled release strategy to avoid solid CO2 formation inside the vessel and through the valve. Graphical Abstract: ga1 Highlights: This study is about techno-economic analysis of CO2 compression process. The boundary pressure was estimated through modeling of CO2 re-injection pipeline. Four different options for compressing CO2-rich stream were suggested. LCC for each option was estimated based on equipment cost and utility consumption. Experimental investigation of blowdown in CO2 distillation column was conducted.